A’barumbung (mandi uap) dalam tradisi pernikahan di pulau Kodingareng Makassar - Akilah Nurul Amalia; Yuni Jelita Sari; Antonius Antonius (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2026)
Appa botting in makassarese means to carry out a marriage ceremony, while the term peerkawinan in bugis means to take each other, thus Marriage is a reciprocal bond between two peoplw of sifferent genders to establish a partnership. The a’barumbung tradition in Makassar is a steam bath procession carried out by the prospective bride as part of a traditional wedding ritual, which lest for three days and has deep meanings such as cleanliness, physical and spiritual preparation, and a symbol of self-purification before entering the gate of marriage. In general, this tradition is usually specifically carried out by the prospective bride as part of a series of a Appasili bunting (siraman) events, but on Kodingareng Island it is usually also carried out for the prospective groom with the aim of purifying himself and preparing himself physically and mentally for married life. The release of water from the body during this steam bath procession is interpreted as the removal of “bad things” and self-purification. A’barumbung is part of the local culture of the Makassar tribe which is still maintained in the traditional wedding procession. A’barumbung means a steam bath that is performed three days before the wedding ceremony for the prospective groom and bride. At this stage, several tools and materials need to be prepared, such as sarongs, blankets, chairs, pans, lellung, and several types of fragrant leaves. Then, the prospective bride and groom sit on chairs, where hot water has been stored with a mixture of fragrant leaves. The bride and groom are covered with several layers of sarongs or blankets. When the A’barumbung procession begins, sever family members will perform angaru (a ritual ablution) in front of the prospective bride and groom. Basically, the culture or tradition implemented and carried out by the people of Kodingareng Island are closely related to beliefs originating from their ancestors. As we already know, Kodingareng Island is the region of the Bugis-Makassar ethnic group.